Bahasa Arab dan Asal-Usulnya: Tinjauan Teoritis - Jezy, Ahmad; Apip, M; Gunawan, Hendra; Rifaldi, Muhammad; Agustiar, Agustiar (IAIN Bone, 2025)
This article discusses the origins of Arabic from a theoretical perspective by examining various linguistic theories and developing religious views. Arabic as part of the Semitic clan has a long history that is closely related to the development of civilization in the Arabian Peninsula. With a literature study approach, this article explores popular theories about the origins of human language, such as divine theory, onomatopoetic theory, interjection theory, social pressure theory, and others, and relates it to the development of the Arabic language. In addition, this article discusses two main views on the origin of Arabic, namely that the language originated from the time of the Prophet Adam AS or developed from the Semitic language family. The results of the study show that the Arabic language has a rich phonetic system and distinctive structure, as well as a privileged position in the context of religion, culture, and history of Muslims. Based on theoretical studies, there are two main opinions about its origins: first, that Arabic originated from the Prophet Adam AS, and second, that Arabic evolved from an older branch of the Afrosiatic-Semic family. The second opinion is supported by stronger linguistic evidence